PROBLEM-BASED LEARNING DIGITAL MODULE ASSISTANCE OF NUMERATION OF PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Via Yustitia; Dian Kusmaharti (Universitas PGRI Yogyakarta, 2022)
The researcher conducted a study to determine the effectiveness of the PBL model assisted by digital modules on the numeracy of elementary school teacher candidates. Numeracy is needed to face the challenges of the future. However, there are many prospective elementary school teachers whose numeracy is still low. The application of the Problem Based Learning (PBL) learning model assisted by digital modules can be used to improve numeracy. This study was conducted to determine the effectiveness of the PBL model assisted by digital modules on numeration. This research is a quantitative experiment on students of PGSD University PGRI Adi Buana Surabaya. The method used is a test. The instrument is a valid and reliable enumeration test. The study results stated that the PBL model assisted by a digital module was effective for numeracy. The effectiveness is shown from the results of the numeracy test.